Uncovering two kinetic factors in the controlled growth of topologically distinct core–shell metal–organic frameworks. Issue 33 (8th July 2019) - Wang, Fang; He, Sanfeng; Wang, Hongliang; Zhang, Songwei; Wu, Chunhui; Huang, Haoxin; Pang, Yuqian; Tsung, Chia-Kuang; Li, Tao
Abstract : Core–shell MOF composites containing uniform Zr/Hf-MOF shells are constructed using kinetic control. Abstract : Constructing core–shell metal–organic frameworks (MOFs) based on two topologically distinct MOFs is a great way to increase MOF material complexity and explore their new functions. However, such a nucleation process is energetically less favored compared to epitaxial growth due to mismatched unit cell parameters. Here, two kinetic factors, nucleation kinetics and dissolution kinetics, are revealed to be two key factors in overcoming this challenge. Through kinetic control, we demonstrate the growth of 4 types of Zr/Hf-MOF shells uniformly and contiguously on 7 different core MOFs including ZIF-8, an acid labile core. Taking advantage of the modular synthesis of Zr-MOFs, we demonstrate that post-synthetic covalent surface modification on a non-functionalizable MOF surface can be made possible through core–shell construction. We also demonstrated that the size selective catalytic behavior can be systematically tuned through changing either the ligand length or ligand functionality.